EXPLORING THE OUTCOMES OF INTERNAL MARKETING: A SYSTEMATIC LITERATURE REVIEW - Juanna, Andi; Mohamad Rizan; Setyo Ferry Wibowo (Universitas Sahid, 2026)
Internal marketing has increasingly attracted scholarly attention as an organizational approach that treats employees as internal customers and seeks to enhance employee-related and organizational outcomes through communication, support, development, empowerment, and alignment with organizational goals. Among these outcomes, job satisfaction has emerged as one of the most frequently examined and strategically important constructs because of its close relationship with employee retention, engagement, performance, and well-being. This study aims to systematically review and synthesize the existing literature on internal marketing and its outcomes, with particular emphasis on job satisfaction and related employee outcomes. A systematic literature review approach was employed using the Publish or Perish application to retrieve records indexed in the Scopus database. The search process used the keywords “job satisfaction” AND “internal marketing,” “job satisfaction” AND “internal market orientation,” and “internal marketing” AND “job satisfaction in service industry.” The initial search identified 124 records. After applying eligibility criteria and PRISMA-based screening procedures, 24 articles published between 2018 and 2024 were selected for in-depth analysis. The findings indicate that internal marketing consistently contributes positively to job satisfaction and is also associated with organizational commitment, work engagement, customer orientation, task performance, employee retention, and broader well-being outcomes. The review further shows that internal marketing is commonly operationalized through dimensions such as empowerment, communication, work environment, development, compensation, vision, and organizational support. Overall, the study confirms that internal marketing should be viewed as a strategic organizational framework with significant implications for both employee satisfaction and wider organizational effectiveness.